2020
DOI: 10.1002/cbdv.201900697
|View full text |Cite
|
Sign up to set email alerts
|

A New Alkaloid from the Aerial Parts of Bupleurum chinense DC.

Abstract: A new isoalloxazine alkaloid, named bupleurine A (1), along with five known compounds (2–6), were isolated from the aerial parts of Bupleurum chinense DC. The structure elucidation of the new alkaloid (1) was employed by combining NMR and HR‐MS data with comparison of reference in the literature. Five known compounds (2–6) were isolated from Bupleurum genus for the first time. Additionally, their antiproliferative activities on HeLa cells were evaluated by MTT assay and IC50 of compounds 1 and 4–6 were below 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…B. chinense , belonging to the plant family Bupleurum spp., was a well-known traditional Chinese medicine (TCM) that had been used for more than a thousand years, distributed mainly in Heilongjiang, Liaoning, Jilin, and Neimeng province of China [ 4 ]. It was reported that the B. chinense and their aerial parts had similar chemical components and pharmacological effects have a good therapeutic effect on epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…B. chinense , belonging to the plant family Bupleurum spp., was a well-known traditional Chinese medicine (TCM) that had been used for more than a thousand years, distributed mainly in Heilongjiang, Liaoning, Jilin, and Neimeng province of China [ 4 ]. It was reported that the B. chinense and their aerial parts had similar chemical components and pharmacological effects have a good therapeutic effect on epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…was rich in resources, and its composition and pharmacological action were similar to that of Bupleurum chinense DC. [ 11 ]. The B. chinense DC.…”
Section: Introductionmentioning
confidence: 99%